Molecular characterization of carbapenem-resistant and virulent plasmids in Klebsiella pneumoniae from patients with bloodstream infections in China - Yongqiang Yang; Yanxian Yang; Guanping Chen; Minmin Lin; Yuan Chen; Ruowen He; Klibs N. Galvão; Mohamed Abd El-Gawad El-Sayed Ahmed; Adam P. Roberts; Yiping Wu; Lan-Lan Zhong; Xiaoxue Liang; et al. (Emerging Microbes and Infections)
Bloodstream infections (BSIs) caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) are potentially life-threatening and an urgent threat to public health. The present study aims to clarify the characteristics of carbapenemase-encoding and virulent plasmids, and their interactions with the host bacterium. A total of 425 Kp isolates were collected from the blood of BSI patients from nine Chinese hospitals, between 2005 and 2019. Integrated epidemiological and genomic data showed that ST11 and ST307 Kp isolates were associated with nosocomial outbreak and transmission. Comparative analysis of 147 Kp genomes and 39 completely assembled chromosomes revealed extensive interruption of acrR by ISKpn26 in all Kp carbapenemase-2 (KPC-2)-producing ST11 Kp isolates, leading to activation of the AcrAB-Tolc multidrug efflux pump and a subsequent reduction in susceptibility to the last-resort antibiotic tigecycline and six other antibiotics. We described 29 KPC-2 plasmids showing diverse structures, two virulence plasmids in two KPC-2-producing Kp, and two novel multidrug-resistant (MDR)-virulent plasmids. This study revealed a multifactorial impact of KPC-2 plasmid on Kp, which may be associated with nosocomial dissemination of MDR isolates.